2021
DOI: 10.1080/1068316x.2021.1962870
|View full text |Cite
|
Sign up to set email alerts
|

The optimal application of empathy interventions to reduce antisocial behaviour and crime: a review of the literature

Abstract: In recent decades, the relationship between weak empathy and the development of antisocial and offending behaviours has been well established. In the first review of its kind, this paper outlines the current implementation of empathy intervention programmes in a variety of disciplines. This paper will identify some key agents that are instrumental in empathy development and build a case to suggest that where such traditional sources of empathy development are inadequate, interventions are crucial to bridge the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 140 publications
(224 reference statements)
0
16
0
Order By: Relevance
“…This suggests that restorative interventions will be less effective with violent offenders and those who are deficient on empathy. Trivedi-Bateman and Crook (2022) argue that interventions are needed that focus on developing empathy. However, while the guilt and shame scales used in Trivedi-Bateman’s (2015) research did make some wider reference to others beyond the victim, such as family and friends, the emphasis of these measures was on the offender being observed by these people in their lives or of them being aware of their wrongdoing, rather than there being a focus on negative impacts of their behaviour for their families and communities.…”
Section: Restorative Practices and Peer Supportmentioning
confidence: 99%
“…This suggests that restorative interventions will be less effective with violent offenders and those who are deficient on empathy. Trivedi-Bateman and Crook (2022) argue that interventions are needed that focus on developing empathy. However, while the guilt and shame scales used in Trivedi-Bateman’s (2015) research did make some wider reference to others beyond the victim, such as family and friends, the emphasis of these measures was on the offender being observed by these people in their lives or of them being aware of their wrongdoing, rather than there being a focus on negative impacts of their behaviour for their families and communities.…”
Section: Restorative Practices and Peer Supportmentioning
confidence: 99%
“…The research aimed to determine whether strengthening morality and emotion management could curtail antisocial behavior and crime. The link between law‐relevant morality, emotional functioning, and crime is well‐evidenced (Pauwels et al, 2018; Trivedi‐Bateman, 2021; Trivedi‐Bateman & Crook, 2022; Wikström et al, 2012). What is less understood is the ways in which morality can be strengthened in adolescence by participation in innovative, evidence‐led, moral, and emotion development programs (more information about The Compass Project can be found at https://lboro.ac.uk/research/compass-project/).…”
Section: The Compass Project (Tcp)mentioning
confidence: 99%
“…These outcomes include improved quality of relationships with others, increased helping and prosocial behaviours, reduced antisocial behaviour and delinquency, reduced contact with criminal justice system-related organisations and less time spent in crime-conducive settings. Evidence indicates that morality development can be compromised in situations characterised by unstable or inconsistent parental modelling, poor parental attachment and certain parental disciplinary styles (Trivedi-Bateman and Crook, 2022). Morality strengthening programmes can potentially address these earlier life experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the term "low functioning" is not a value judgement and instead corresponds to the scale score.4. Reviews of other existing literature that evidence associations between morality, emotion and crime using a variety of theoretical approaches, qualitative and quantitative methodologies and diverse study samples can be found elsewhere(Trivedi-Bateman 2015, 2021, Trivedi-Bateman and Crook, 2022.5. The project and the consent procedure were approved by the Loughborough University Ethics Review Committee (2022-7834-9130) on 13 April 2022.…”
mentioning
confidence: 99%